Analysis of the Songgot Menyonggot Tradition in the Tanjung Balai Community - Sindy Pratiwi; Ahmad Bengar Harahap (Asian Journal of Applied Education (AJAE), 2024)
This research aims to analyze the meaning of the songgot menyonggot tradition and provide an explanation related to the symbols of the songgot menyonggot tradition in the Tanjung Balai community. The method used in this research is descriptive qualitative, the research location was carried out in Tanjung Balai, precisely in Batu 3 SiJambi. To analyze the data using Piercer's semiotic theory, namely by analyzing icons, indices and symbols related to the songgot menyonggot tradition. Based on the results of the research conducted, it can be concluded that this tradition is a tradition that aims to provide spiritual strength, motivation and prayers given by families or community groups to someone who is experiencing or has experienced a disaster.